Development of adaptive experiential learning via interactive contemporary education with extended reality (B) - Lau, Jia Xian (2019)
With Ministry of Education (MOE) constant effort made for the further incorporation of technology into Singaporean’s learning. Dyslexia Association of Singapore (DAS) has started to tap on technological solution to make dyslexic students’ learning experience more interactive. DAS has utilised technology such as Raz-Kids application and interactive whiteboard. Furthermore, with the influx in intake from 350 students in Year 2003 to 3500 students in Year 2018 in DAS learning centres, some learning centres are reaching their full capacity and facing a strain in resources. To improve the dyslexic learner’s practice environment and mitigate the challenges of huge influx in student’s intake faced by DAS, the Virtual Reality (VR) solution was developed. It provides a realistic virtual presentation simulation environment that caters to the dyslexic learners’ need. The software in this project was developed using Unity3D game development engine, Microsoft Azure cloud technology and HTC Vive. This software allows students to hear the correct pronunciation of words to be used in their presentations from the software. Students can also be assessed by the software on various oral presentation aspects such as eye contact, volume and pronunciation. This report will be focusing on the development of this software on Unity3D, which includes coding of assessment features with C# scripts and the implementation of storage of assessment data generated by the game locally in the computer’s drive.